Historical Review of Russian National Policy in the North Caucasus - Vladimirovna Malyshkina, Elena; Nikolaevna Goroshko, Olga; Alekseevna Bondar, Irina; Gorčev, Jordan P. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
In this article, the authors tried to trace in a wide historical and ethno-political context of the development of Russian national policy exemplified by the republics of the North Caucasus at different time stages, having done so on the basis of the most representative range of sources. Comprehended in the historical dynamics of domestic and international experience, special attention is paid to those items that can be used to develop the foundations of the national policy of the Russian Federation in the North Caucasus at the present stage. In this regard, new aspects and provisions have been identified in the following areas: Russian (imperial and Soviet) experience in managing the North Caucasus region; the impact of changes in nation-building on the ethno political processes in the region; ethno political processes in the post-Soviet period and features of their manifestation in the republics of the North Caucasus; modern political processes in the North Caucasus in the context of Russian federalism; main problems and the contradictions of the Russian model of federalism; the experience of state authorities in the regulation of inter-ethnic relations in the region; possible scenarios for the development of federative relations in Russia and ways to optimize them are presented.
Keywords: ethno political processes; national policy; national relations